2022
DOI: 10.1089/jop.2021.0067
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lipid Metabolism for the Treatment of Age-Related Macular Degeneration: Insights from Preclinical Mouse Models

Abstract: Age-related macular degeneration (AMD) is a major leading cause of irreversible visual impairment in the world with limited therapeutic interventions. Histological, biochemical, genetic, and epidemiological studies strongly implicate dysregulated lipid metabolism in the retinal pigmented epithelium (RPE) in AMD pathobiology. However, effective therapies targeting lipid metabolism still need to be identified and developed for this blinding disease. To test lipid metabolism-targeting therapies, preclinical AMD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 316 publications
0
31
0
Order By: Relevance
“…Dysregulation in lipid/cholesterol homeostasis is linked to age-related diseases and loss of RPE function [ 55 , 56 , 57 ]. Several features observed in the LC3b −/− RPE, such as reduced phagocytosis, lipid deposits, recruitment of immune cells, and complement pathway activation are reminiscent of AMD-like pathophysiology [ 28 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation in lipid/cholesterol homeostasis is linked to age-related diseases and loss of RPE function [ 55 , 56 , 57 ]. Several features observed in the LC3b −/− RPE, such as reduced phagocytosis, lipid deposits, recruitment of immune cells, and complement pathway activation are reminiscent of AMD-like pathophysiology [ 28 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…What role this gene editing activity plays in RPE-specific β-lipoproteins assembly is unknown. Further studies are necessary to understand how cholesterol biosynthesis and packaging in lipoproteins is influenced by LAP with an emphasis on therapeutics designed to restore lipid homeostasis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that ANGPTL4 can promote both angiogenesis ( 32 , 42 ) and vascular permeability ( 34 , 41 , 59 ), the latter through promotion of the Rho/ROCK pathway ( 41 ). In addition to regulating angiogiogenesis, ANGPTL4 has also been reported to regulate lipid metabolism ( 60 ) and inflammation ( 61 ), both of which have also been implicated in the pathogenesis of AMD ( 62 , 63 ). Additional studies will be necessary to determine the mechanisms by which ANGPTL4 contributes to the development of CNV in patients with nvAMD.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism is regulated by apolipoproteins, structural proteins essential for the metabolism of triglycerides and cholesterol. Lipoproteins found in the posterior ocular segment are part of a distinct class of lipoproteins similar to very low-density lipoproteins (VLDL) concerning size, but they are structurally similar to LDL, as they are rich in esterified cholesterol [5,18]. Apolipoprotein E (ApoE) was identified as a major drusen component.…”
Section: Dyslipidemia and Its Effects In The Eyementioning
confidence: 99%
“…In lipoproteins, ApoE functions to facilitate their cellular uptake, binding to extracellular matrices, thus allowing efficient delivery and removal of lipids from cells. Besides ApoE, other lipid components were found in drusen composition, such as esterified cholesterol, unesterified cholesterol, phosphatidylcholine, triglycerides, sphingomyelin, fatty acids, and other apolipoproteins [8,18]. The oxidation of these lipids and proteins can contribute to a pro-inflammatory environment, promoting the development of AMD.…”
Section: Dyslipidemia and Its Effects In The Eyementioning
confidence: 99%